INCREASING STAFF ENGAGEMENT: PRACTICAL EXPERIENCE - O. S. Suvalov; T. V. Suvalova (Вестник университета)
The aim of the study is to identify the level of staff interest in the functions and activities of the company. The article substantiates the relevance of increasing staff involvement. The paper considers the results of the study of  the influence of involvement on labor productivity according to the American Institute of Public Opinion Gallup. The  authors highlight the qualities characteristic of the employee involved. The study gives characteristics that  make it possible to talk about the effectiveness of the employees involved. The article notes the “symptoms” of  low engagement, considers the main mistakes made by management that reduce engagement, highlights the  necessary incentives for the fruitful work of the organization’s employees. The authors focuse attention on the criteria for assessing staff involvement and ways to analyse the level of staff involvement. The paper presents the main methods for assessing staff involvement. The study notes the influence of a highly developed moral and  psychological climate on the personnel’s commitment to the core values of the company, the observance of the rules and compliance with established standards. The article emphasizes the role of corporate culture. The paper considers the experience of employee involvement of ABC Supply, Zappos, Reeebok, FullContact companies.